Co-operation or mutual co-option? The Senegal-EU partnership on migration - Mamadou Dimé; Rose Jaji (German Institute of Development and Sustainability (IDOS), 2023)
– This policy brief addresses the tensions between international and domestic interests on issues relating to partnerships on migration governance. It specifically discusses the Senegal-EU partnership on migration, highlighting the unequal relationship between the two partners and the implications of this relationship for the outcomes of migration policy. The authors highlight how the EU's use of funding to shape migration governance in Senegal creates ownership and accountability challenges for policies that are formulated at the initiative of external actors without much, if any, input by the government of Senegal and its people. The Senegalese government's quest to attract funding from the EU through the partnership on migration results in it being more accountable to its external partners, and less accountable to the Senegalese people and local civil society organisations. The latter argue that the government needs to formulate a policy that addresses migration in Senegal in a comprehensive manner. Senegal's financially weaker position vis-á-vis the EU does not, however, constrain the Senegalese government from exercising agency in pursuit of its own interests within the EU agenda. It seeks to strike a balance between the interests of the EU and its domestic priorities on migration. It pursues this goal by conflating rent-seeking behaviour with domestic interests that are at variance with the EU agenda - a strategy facilitated by the government's reluctance to adopt and commit to an official document providing the framework for migration governance. The partnership between Senegal and the EU has the hallmarks of an interface characterised more by mutual co-option than by meaningful co-operation on international migration governance norms. This state of affairs is detrimental to the formulation of a comprehensive migration policy addressing various aspects of Senegal's complex migration matrix. In order for the Senegal-EU partnership to go beyond the pursuit of narrow interests and address migration governance issues in a comprehensive manner, several changes are required. - Donor states, especially in the EU, need to acknowledge the variety of migration challenges Senegal is facing, and not limit their action to their own border externalisation interests. Instead of only engaging with the government, and a few "token" civil society organisations, funders need to take on board the views of significant civil society and local government actors who are more in touch with local realities. - A holistic migration policy is urgently needed, which goes beyond the current focus, required by external actors, on emigration from Senegal. Such a migration policy has become even more indispensable to Senegal because of the Senegalese diaspora's economic and political role in the country, its contribution to Senegal's development, and the need for the Senegalese government to provide adequate responses to the diaspora's needs. Such a policy is also needed because of the position of Senegal as a destination country for migrants from the West African subregion. - The EU needs to transform its current approach to "partnerships" on the governance of migration to a model that is mutually beneficial. The current partnership functions as a vehicle through which the EU and its Member States pursue their own agenda. A more feasible partnership would entail identification of the partners' respective priorities and co-operation on areas of mutual interest.
Keywords: 320